Price reactions when consumers are concerned about pro-social reputation - Goytom Abraha Kahsay; Laura Mørch Andersen; Lars Gårn Hansen (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2014)
In this paper, we propose a reputation-signalling model of demand for consumer goods containing pro-social characteristics such as a 'fair trade' or 'organic' certification. We show that reputation signalling can reverse price reactions resembling the crowding-out of pre-existing motives for pro-social behavior seen in situations of volunteering and charitable giving. Finally, using a unique combination of questionnaire and purchase panel data, we present evidence of such reputation-driven reversal of price reactions in the Danish market for organic milk.
Keywords: D03; D11; D12; D64; D82; D51; 330; net-crowding out; reversed price reactions; pro-social reputation; reputation signalling; consumer goods